Experiences of registered nurses of their role in carrying out the induced sputum procedure in diagnosing childhood Tuberculosis - Isaacs, Whasiefa (Division of Nursing and Midwifery, 2015)
Tuberculosis (TB) is an ancient disease dating back at least 5000 years, but the TB epidemic is said to be getting worse than at any other time in history (Puri & John, 1997: 12). Someone is infected with TB every second, with a death from TB every 15 seconds, and one out of every three of these infections being in a child (Zar, Hanslo, Apolles, Swingler & Hussey, 2005: 130). The purpose of this study was to explore and describe registered nurses' experiences of their role with regard to the induced sputum procedure to diagnose childhood TB.